MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF SEBAGAI PENGUAT MOTIVASI BELAJAR AL-QUR’AN HADIS: STUDI DI MAN 1 BANDAR LAMPUNG - Muhammad Ilham Jaya Kesuma; Agus Jatmiko; Sunarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the need for Al-Qur'an Hadith learning that can respond to developments in the digital era without neglecting Islamic values. The uniqueness of this research lies in the use of interactive multimedia learning media developed directly by Al-Qur'an Hadith teachers at MAN 1 Bandar Lampung, so that innovation emerges from within the madrasah and does not adopt external platforms as is often found in similar studies. This study aims to describe the implementation of interactive multimedia media, students' learning motivation after using it, and the relationship between the two in the context of Al-Qur'an Hadith learning. The approach used is qualitative with a case study design. Data were obtained through observation, interviews, and documentation involving teachers, students, and madrasah officials. Data analysis follows the Miles, Huberman, and Saldana model which includes data reduction, data presentation, and drawing conclusions. The validity of the findings is strengthened through triangulation of sources, techniques, and time. The results show that interactive multimedia media is implemented through careful planning, participatory implementation, and evaluation that emphasizes digital feedback. This media has been proven to increase student learning motivation through a combination of visual and audio, a systematic pedagogical flow, gamification elements in digital quizzes, and interactive features that make learning more engaging and spiritually meaningful. The study concluded that the integration of interactive multimedia media can strengthen student engagement and motivation in studying the Quran and Hadith, while also serving as a relevant model for digital learning innovation for madrasas in the technological era.